[Editorial] Special issue on computational intelligence and nature-inspired algorithms for real-world data analytics and pattern recognition - Cagnoni, Stefano (2018)
Cagnoni, S., & Castelli, M. (2018). [Editorial]. Special issue on computational intelligence and nature-inspired algorithms for real-world data analytics and pattern recognition. Algorithms, 11(3), 1-2. DOI: 10.3390/a11030025